The acute effects of dynamic and static stretching on tennis serve targeting performance - Turna, B.; Sahan, A.; Yilmaz, B. (Journal of Education and Training Studies, 2019)
The study investigates the acute effects of dynamic and static stretching on the tennis serve targeting performance of amateur tennis players. Twenty male athletes who were between the ages of 16-24 years and played tennis for at least 1 year (21.40±2.16 years, 181±0.06 cm, 71.85±7.42 kg, tennis playing time 1.55±0.88 years) voluntarily participated in the study.